2015
DOI: 10.3390/ijerph121214984
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of a Forest Therapy Program on Middle-Aged Females

Abstract: The natural environment is increasingly recognized as an effective counter to urban stress, and “Forest Therapy” has recently attracted attention as a relaxation and stress management activity with demonstrated clinical efficacy. The present study assessed the physiological and psychological effects of a forest therapy program on middle-aged females. Seventeen Japanese females (62.2 ± 9.4 years; mean ± standard deviation) participated in this experiment. Pulse rate, salivary cortisol level, and psychological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
167
3
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(230 citation statements)
references
References 28 publications
21
167
3
5
Order By: Relevance
“…Taking ordinary people as participants, it was found that their anxiety can also be alleviated in 1-2 days (Park et al 2007, 2011, Lee et al 2009, Ochiai et al 2015. In addition, young adults and middle-aged hypertensive patients can even perceive less anxious in a 15-min long forest bathing (Song et al 2013(Song et al , 2015. These results together suggest that forest bathing had the potential of short-term effect on anxiety of ordinary healthy people.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Taking ordinary people as participants, it was found that their anxiety can also be alleviated in 1-2 days (Park et al 2007, 2011, Lee et al 2009, Ochiai et al 2015. In addition, young adults and middle-aged hypertensive patients can even perceive less anxious in a 15-min long forest bathing (Song et al 2013(Song et al , 2015. These results together suggest that forest bathing had the potential of short-term effect on anxiety of ordinary healthy people.…”
Section: Introductionmentioning
confidence: 91%
“…It was found that spending time in a forest can effectively reduce mental stress and alleviate anxiety (Morita et al 2007, Kim et al 2009, Park et al 2011, Ochiai et al 2015, Song et al 2016, Chun et al 2016. This function was recognized as the term of "forest bathing", i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the confounding effects (e.g., noise) may influence the impacts of the intervention. Many of the previous studies also used small sample sizes to avoid the abovementioned drawbacks while discerning the influences of forest bathing on health [15,24,25]. For example, Lee et al [15] recruited twelve adult males, and Ochiai et al [25] included nine middle-aged men to investigate the effects of forest bathing.…”
Section: Participantsmentioning
confidence: 99%
“…Water is additionally associated with positive impacts to human perceptions of aesthetics, increased biodiversity, and increased urban quality of life (Völker & Kistemann, 2011;Cooper et al, 2017). Other studies on human well-being have focused on forested landscapes, suggesting recreational areas with high amounts of "greenness" may be associated with higher human well-being benefits Tsunetsugu et al, 2007;Tsunetsugu et al, 2010;Lee et al, 2011, Ochiai et al, 2015.…”
Section: Introductionmentioning
confidence: 99%